EPIDEMIOLOGY OF BACTERIA COLONIZATION AND ICU-ACQUIRED INFECTION IN A NIGERIAN TERTIARY HOSPITAL - Sanusi, Arinola A; Osinaike, Babatunde B; Fayemiwo, Samuel Adetona; Nwadike, Victor U; Akinyemi, Akinola O; Adigun, Tinuola A; Olusanya, Olawale O; Bakare, Rasheed A (African Journal of Infectious Diseases (AJID), 2015)
Background: Health care associated infection (HCAI) or Hospital acquired infection is associated with significant morbidity, mortality and cost. The incidence is about 6% and disproportionately higher in critically ill patients who may have been immune-compromised with many invasive procedures already performed. Prevention of HCAI and appropriate management of patients in the intensive care unit (ICU) requires knowledge on the pattern of microbial colonization and infections. The aim of this preliminary study was to provide current data on the pattern of ICU acquired infections in our hospital. Patients and Methods: It was a cross sectional study of patients admitted into the ICU who were expected to stay longer than 48hrs between July 2011 and September 2012. Urine, blood, and tracheal aspirate were collected on days 1, 3 and 5 for microbiological studies. All patients involved in the study had urethral catheter in-situ and received mechanical ventilation in the ICU. Results: Fifty-nine patients were recruited into the study. The mean age of the patients was 30.08 + 19.9yr; while the reasons for admissions were respiratory failure (59.3%), cardiovascular instability, trauma and neurological diseases. About 30% of the samples taken from the study sites on arrival in the ICU had positive culture yields. Organisms cultured included Klebsiella oxytoca, Staphylococcus aureus, and Pseudomonas aeruginosa. The urinary tract had the highest number of isolated organisms- 9(60%), followed by equal number of isolated organisms-3(20%) in the blood and respiratory tract. Eleven (73.3%) of the organisms isolated were Gram-negative bacteria, and 4 (26.7%) were Gram-positive cocci. The commonest bacteria isolates were Staphylococcus aureus (4/26.7%) and Klebsiella oxytoca (4/ 26.7%). A total of 15 ICU- acquired infections were detected in 9 of 59 patients. Conclusion: The HCIA infection rate was 15%, and urinary tract infections (UTI) was the commonest hospital acquired infection in our ICU. Klebsiella oxytoca and Staphylococcus aureus were the commonest organisms.